Intestinal gas retention in patients with idiopathic slow-transit constipation - Hernando-Harder, Ana C.; Franke, Andreas; Wedel, Thilo; Böttner, Martina; Krammer, H.; Singer, Manfred V.; Harder, Hermann (Digestive diseases and sciences, 2007)
Patients with slow-transit constipation (STC) have delayed colonic transit for solid und liquid bowel contents but intestinal gas handling has not been studied so far. Different nutrients influence motor and sensory gut function. We hypothesized that, in patients with STC, alteration of regulatory mechanisms may result in impaired intestinal gas dynamics. On 3 separate days, validated gas challenge was performed in 10 STC patients and 10 volunteers during duodenal saline, lipids, or intravenous glucose. During saline only 60% ± 8% of gas was cleared by STC patients after 60-min gas infusion, vs. 91% ± 2% by controls (P < 0.001). Acute hyperglycemia or lipids did not change intestinal gas dynamics in these patients (saline infusion), but compared to healthy subjects, significant intestinal gas retention occurred. In STC, disturbances of intestinal gas dynamics include basal intestinal gas retention, and this is virtually not affected by acute hyperglycemia or duodenal lipids.
Gesehen am 16.03.2022